Hubungan Islam dan Politik yang Mungkin di Indonesia - Thaha, Idris (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2006)
The theme of the articles written by Effendy in this book is a response to the developments in the relationship between Islam and politics in Indonesia. Effendy argues that a link between lslam and politics has occurred since the earliest days of Islam in Indonesia. Historically, political nuances have been deeply influenced by dakwah islamiah, or Islamic propagation, in this countryDOI: 10.15408/sdi.v13i2.572